Peningkatan Pengetahuan Faktor-Faktor yang Memengaruhi Perilaku Seks dalam Upaya Cegah Seks Pranikah pada Siswa-Siswi SMP N 77 dan SMA N 77 Jakarta Pusat - Tri Panjiasih Susmiarsih; Himmi Marsiati; Susi Endrini (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2019)
ABSTRACT The premarital sex behavior is a problem and social phenomenon that is increasingly prevalent in society. At a young age, the premarital sex should be a major concern to reduce pregnancy rates unintended, sexually transmitted diseases, school drop out, abortion and even a death. One effort to prevent the premarital sex behavior for students in schools with methods of providing knowledge about sexual behavior, reproductive health, an understanding of religious and the early marriage law. Evaluation of indicators usingpre test and post test data that are analyzed with paired t and regression test. The results show that after counseling, the knowledge of junior high school students about sexual behavior, reproductive health and religious knowledge increased significantly (p <0.05), while high school students of religious knowledge and early marriage law increased significantly. Keywords: premarital sex; reproductive health; sexual behavior